Making Compost Using Organic Solid Waste - Cahaya, Andhika; Nugroho, Dody Adi (Universitas Pakuan, 2023)
This research using the vegetables garbage, baggase, and goat dirt. The research quickened with addition of EM-4 bacterium. The variation of research is, mixture between vegetables garbage and goat dirt (variable A), vegetables garbage and baggase (variable B), baggase and goat dirt (variable C),and the last mixture betwen vegetables garbage, baggase and goat dirt. All the variable added by 10 ml of EM-4 bacterium. Research conducted by aerobic method. Conclusion obtained from this research is the mixture of vegetables garbage and goat dirt (variable A) more easily becoming compost than other variable. Require to be underlined, addition of baggase into variable B, C, and D cause the mixture more difficult become compost. Compost maturity seen from C/N ratio. C/N ratio of compost variable A is 17.45, this is according to value of compost quality at SNI 19-7030-2004. Usually compost experience of the maturation in 30 day, but in mixture with baggase the time of maturation is longer.